Strengthening 3D Model Design Learning by Utilizing Website-Based Onshape 3D to Improve the Competence of Students at SMKN Jateng in Semarang - Bahatmaka, Aldias; Darsono, Febri Budi; Irawaty; Prasdika, Tegar Oki; Laksono, Aryo; Habibullah, Muhammad; Muclisin, Choirul Anton (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service is an implementation of science in the field of Design / Engineering, especially 3D object design. The Indonesian creative industry sees great opportunities with 3D design. This is closely related to the development of information technology that is increasing every year. Knowing how to create 3D objects will open up job opportunities for the current generation. In addition, it is also one way to attract scientific interests to the University level, especially in the Mechanical Engineering Department. In facing increasingly fierce global competition, it is very necessary The purpose of this community service program is to provide training in creating 3D objects to vocational school students because there is no comprehensive training on the process of creating 3D objects and their supporting tools. as an effort to improve design skills and also at the same time capture students' interests and talents to be able to learn early about one of the sciences in the Mechanical Engineering Department. 3D object design begins with how to create 3D objects with website-based Onshape3d. Onshape3d with a website was chosen because it is open source or free. Onshape3d's ability to create 3D objects and create 3D animations has long been recognized, because it is open source. To prevent creativity support from becoming a burden, it is hoped that this will become a source of innovation for participants. To assess the effectiveness of the training, student understanding was evaluated through Quizizz before the pre-test and after the post-test of the activity. The pre-test results showed that students' initial understanding of 3D design concepts and CAD software was still relatively low, with an average score of 45%. Their knowledge was still limited to the basic functions of modeling software. After the training, the post-test evaluation showed a significant improvement: the average score jumped to 76%, reflecting a better understanding of 3D design concepts and skills in using OnShape 3D.